Cosmopolitanism as Translation. (December 2014) - Bielsa, Esperança
Whereas globalization theory was predominantly silent about the role of translation in making possible the flow of information worldwide, assuming instant communicability and transparency, translation has gained central importance in recent accounts of cosmopolitanism that emphasize global interdependence and the negotiation of difference. In this context, a specification of translation processes provides a way of analysing the form in which interactions between different modernities take place and of specifying a notion of cosmopolitanism as internalization of the other. This article approaches translation as much more than the linguistic transfer of information from one language to another. Widely defined as the experience or the test of the foreign, a process which mobilizes our whole relationship to the other, translation appears as a material, concrete practice through which cosmopolitanism, conceived as openness to the world and to others, can be empirically examined. After having thus identified the central role of translation in a cosmopolitan context, the article examines how it can be used to approach current notions of aesthetic or artistic cosmopolitanism with reference to the key notion of world literature. Finally, it outlines the most important implications that a conception of cosmopolitanism as translation has for cosmopolitan social theory.